Cell and Molecular Biology What We Know & How We Found Out - Bergtrom, Gerald (Open textbook library., 2023)
CMB5e is the latest edition of an interactive Open Educational Resource (OER) electronic textbook (iText), available under a Creative Commons CC-BY license. Like earlier editions, CMB5e opens with a short history of the discipline and a discussion of scientific method. The book remains focused on the understanding of evolution that informs all of the life sciences and continues to provide experimental support for what we know about cell and molecular biology. Having a sense of how science is practiced and how investigators think about experimental results is essential to understanding the relationship of cell structure and function, not to mention the natural world around us. CMB5e is available in three versions (plus a sample chapter): In each chapter of the Basic CMB5e iText, an introduction includes learning objectives and context-embedded links to short explanatory voice-over PowerPoint recordings (VOPs) and other web-links of interest. QR codes allow the reader just-in-time access to the VOPs on smart phones or any camera-enabled portable device. The Annotated CMB5e adds pre-written, interactive context-embedded Challenge boxes to the Basic version of the book. These contain open-ended questions that expand on text readings. Any or all of them can be the basis of informal class and online discussion or as graded assignments. The Instructor’s CMB5e iText adds a series of 25 Words or Less essay questions that the author used as short (i.e., easy to grade!) writing assignments to strengthen student’s critical thinking and writing skills. A CMB5e Sample Chapter. The Art and Illustration Resource for Cell and Molecular Biology contains high resolution JPGs of figures in all CMB5 digital and print versions. JPGs are all public domain or CC-BY licensed (a source list is included).